The economics book - Kishtainy, Niall; Abbot, George (DK Publishing, 2012)
"Reveals the many ideas and schools of economics that have emerged since trading first began in ancient times."--Ze záložky
Životopisné údaje
Terminologický slovník
Obsahuje rejstřík
Keywords: ekonomie; hospodářské dějiny; ekonomové; economics; economic history; economists; populárně-naučné publikace; popular works